Efficiency of high-intensity therapy with rosuvastatin for secondary prevention of cardiovascular complications in patients with a very high risk - Kolmakova, T. E.; Alekseeva, I. A.; Tmoyan, N. A.; Ezhov, M. V. (Aterotromboz (Online), 2022)
According to the latest international and Russian guidelines for the treatment of dyslipidemias, statins are defined as the main group of drugs that significantly reduce the level of low-density lipoprotein cholesterol (LDL-C) effectively prevent atherosclerotic cardiovascular diseases (CVD) and complications and can slow down the progression of atherosclerosis. The principle “the lower LDL-C, the better” is especially relevant in categories of patients with very high and extreme cardiovascular risk, and therefore, in order to achieve target LDL-C values (≤1.4 is optimal ≤1.0) in this category of patients, high-intensity lipid-lowering therapy should be used. Rosuvastatin remains the most effective statin. Its use makes possible to achieve target lipid values at the starting dose of treatment, enhances adherence to treatment, and also reduces the frequency of side effects associated with the use of high doses of other statins. In addition, the proven ability of rosuvastatin to reduce the volume of atherosclerotic plaque, by reducing the level of pro-inflammatory cytokines and C-reactive protein, normalizing endothelial function, antiplatelet action, that is, rosuvastatin, in addition to its powerful lipid-lowering effect, has anti-inflammatory and anti-ischemic effects. Also, rosuvastatin can be successfully used in the presence of comorbidities, including chronic kidney disease and chronic heart failure. Taking into consideration the urgency of the fight against the COVID-19 pandemic (coronavirus Disease 2019), which covered 220 countries, due to the lack of effective etiotropic drugs, the possibility of using statins, including rosuvastatin, for the treatment of comorbid patients with COVID-19, was evaluated.